Longitudinal Predictors of Alcohol‐Related Harms During the Transition to Adulthood. (22nd February 2013) - Little, Keriann; Hawkins, Mary T; Sanson, Ann; O'Connor, Meredith; Toumbourou, John W; Smart, Diana; Vassallo, Suzanne
<x xml:space="preserve">Abstract</x> While a range of factors have been found to increase the likelihood of alcohol‐related harms among young people, little is known about their relative importance. This article aimed to identify the risks for alcohol‐related harms at an age when alcohol use and problems tend to peak in Australia (19–20 years). A wide range of concurrent and antecedent factors from multiple domains were examined using path analysis, including individual characteristics, family environment, and externalising and internalising problems. The sample comprised of 941 individuals from the Australian Temperament Project, a large longitudinal community‐based study. The path model controlled for current risky drinking and revealed a number of variables that were significant longitudinal predictors of alcohol‐related harms within each of the domains, including adolescent antisocial behaviour and drinking behaviour, low agreeableness, impulsivity, and paternal drinking levels. The potential for developmental prevention approaches to reduce alcohol‐related harms by targeting externalising behaviour problems, interpersonal influences, and individual characteristics is discussed.